Comparative analysis of marine-protected area effectiveness in the protection of marine mammals: Lessons learned and recommendations - Grau Tomás, Estela; García Sanabria, Javier (Frontiers in Marine Science, 2022)
The aim of this study is to assess MPA's effectiveness in the protection of marine mammals. For this purpose, this study analysed the long-term population trend of four different species of marine mammals, geographically placed in distant MPAs. In addition, matching biophysical and governance indicators were identified, in order to relate the management approaches to the biological effectiveness or ineffectiveness. The results show population recovery trends, providing empirical shreds of evidence that suggest the effectiveness of area-based protection measures in marine mammals. Moreover, a parallelism between the governance indicators and the biophysical ones, supports that biological and management effectiveness are interrelated. On this basis, the biophysical indicator of human impact was discussed to be deeply related to the precautionary principle, and perhaps less efficient than the adaptive management. Finally, this study highlights the necessity to better monitor the effectiveness of marine protected areas in order to avoid paper parks and suggests future recommendations.